Development of Gastro-Retentive Combination Formulation of Montelukast Sodium and Ketotifen Besilate for Allergic Rhinitis and Asthma - Dangi, Satyawan Singh; Agrawal, Om Prakash (Journal of Neonatal Surgery, 2025)
Aim: The study aimed to develop a once-daily sustained-release gastroretentive combination formulation of ketotifen besilate and montelukast sodium using multilayer tablet technology and gastro-retentive systems for the treatment of allergic rhinitis and asthma. Background: Ketotifen besilate and montelukast sodium are commonly used to manage allergic rhinitis and asthma. However, their conventional formulations often require multiple doses per day, leading to poor patient compliance. A gastro-retentive system allowing once-daily dosing could improve adherence and therapeutic outcomes. Materials and Methods: A multilayer tablet was formulated with montelukast sodium in the immediate-release layer and ketotifen besilate in both the immediate- and sustained-release layers, using calcium silicate as a floating agent for gastric retention. Hydroxypropyl Methylcellulose (HPMC) controlled the sustained release of ketotifen, while the addition of super-disintegrants and a surfactant improved the release of poorly soluble montelukast. The lactose-microcrystalline cellulose ratio was adjusted to meet the target dissolution profile and comparative dissolution tests were conducted to assess similarity to the desired release profile. Results: Comparative dissolution tests demonstrated high similarity between the combination formulation and the target release profile, with similarity factor (f2) values of 58.5 and 65.9. The formulation successfully allowed for different release rates of the two active ingredients, improving drug absorption and extending the duration of action. Conclusion: The developed gastro-retentive formulation enabled a transition from twice-daily to once-daily dosing, enhancing patient compliance. The multilayer tablet design efficiently controlled the release profiles of both active ingredients, addressing limitations associated with the absorption sites of each drug.